Formulation and evaluation liquid hand soap of celery leaf (Apium graviolens) extract - Sri Idawati; Dhika Juliana Sukmana (Jurnal Pijar Mipa, 2022)
Washing hands with soap is one of the new habits during the COVID-19 pandemic, which is very important to continue to apply. Therefore, alternative natural ingredients are needed to manufacture liquid hand soap that is safe to use in the long term. Celery leaves contain flavonoids, saponins, tannins, essential oils, choline, lipase, and alkaloids. The content of these secondary metabolites has antimicrobial activity. This study aims to formulate liquid hand soap preparations from celery leaf extract following SNI 2588.2.2017. This research is experimental laboratory research that formulates soap preparations with concentrations of 5%, 10%, and 15% and is followed by an evaluation of the preparations based on the referenced SNI quality requirements. This study resulted in an extract yield of 37.12% with organoleptic test results in a thick liquid dosage form, characteristic odor of celery, and green color. In the evaluation test of preparations based on SNI 2588:2017, the results obtained that liquid hand soap preparations meet the requirements. PH for FI, FII, and FIII respectively 9.4, 9.5, and 9.3. In the total active ingredient test, the FI 34.6% was obtained; FII 32.2% and FIII 32.6%. Then in the ethanol insoluble material test, the FI results were 0.094%, FII 0.086%, and FIII 0.112%. Free alkali test obtained FI 0.044%, FII 0.0472%, and FIII 0.0488%. Then the total plate number test was obtained in FI, FII, and FIII preparations; namely, there was no colony growth in samples with dilutions of 10-1, 10-2, and 10-3. The formulation of liquid hand soap meets the quality requirements of SNI 2588.2.2017.